Three's a crowd : the dynamic of third parties, Ross Perot, & Republican resurgence - Rapoport, Ronald (University of Michigan Press, 2008)
"For those wanting someone to blame for the Republican resurgence that began with the 1994 congressional elections, Rapoport and Stone have an answer: blame the third-party presidential candidacies of H. Ross Perot in 1992 and 1996. They argue that successful third parties at the presidential level have the opportunity to have a substantial impact on the two-party system. The common analogy is that a third party is like a bee: it stings and then dies. The sting hurts one of the major parties. If a third party has a large and identifiable issue constituency, ensuring the major parties' bid for the support of its members, and if the party that 'wins' the third-party supporters is changed, then the 'dynamic of third parties' has contributed to the continued evolution of the American party system. Third parties, as the authors note, appear only when there is unhappiness with one or both of the two major parties. The authors have produced a near-mountain of empirical evidence to support their dynamic of third-parties theory. Summing up: Recommended. General readers, lower-division undergraduates through faculty."--W.K. Hall, Bradley University -- Choice, October 2006